Efficiency of Different Sampling Tools for Aquatic Macroinvertebrate Collections in Malaysian Streams - Wan Mohd Hafezul Wan Abdul Ghani,; Che Salmah Md Rawi,; Suhaila Abd. Hamid,; Salman Abdo Al-Shami, (Tropical Life Sciences Research, 2016)
This study analyses the sampling performance of three benthic sampling tools commonly used to collect freshwater macroinvertebrates. Efficiency of qualitative D-frame and square aquatic nets were compared to a quantitative Surber sampler in tropical Malaysian streams. The abundance and diversity of macroinvertebrates collected using each tool evaluated along with their relative variations (RVs). Each tool was used to sample macroinvertebrates from three streams draining different areas: a vegetable farm, a tea plantation and a forest reserve. High macroinvertebrate diversities were recorded using the square net and Surber sampler at the forested stream site; however, very low species abundance was recorded by the Surber sampler. Relatively large variations in the Surber sampler collections (RVs of 36% and 28%) were observed for the vegetable farm and tea plantation streams, respectively. Of the three sampling methods, the square net was the most efficient, collecting a greater diversity of macroinvertebrate taxa and a greater number of specimens (i.e., abundance) overall, particularly from the vegetable farm and the tea plantation streams (RV<25%). Fewer square net sample passes (<8 samples) were sufficient to perform a biological assessment of water quality, but each sample required a slightly longer processing time (±20 min) compared with those gathered via the other samplers. In conclusion, all three apparatuses were suitable for macroinvertebrate collection in Malaysian streams and gathered assemblages that resulted in the determination of similar biological water quality classes using the Family Biotic Index (FBI) and the Biological Monitoring Working Party (BMWP). However, despite a slightly longer processing time, the square net was more efficient (lowest RV) at collecting samples and more suitable for the collection of macroinvertebrates from deep, fast flowing, wadeable streams with coarse substrates. Kajian ini menganalisa pencapaian tiga alat penyampelan bentik yang selalu digunakan untuk memungut makroinvertebrata air tawar. Kecekapan jaring kualitatif rangka-D dan jaring akuatik segi empat dibandingkan dengan penyampel kuantitatif Surber di sungai tropika di Malaysia. Kepelbagiaan dan kepelbagaian makroinvertebrata yang dipungut menggunakan setiap alat dinilai bersama variasi relatifnya (RV). Setiap alat digunakan untuk menyampel makroinvertebrata dari tiga anak sungai yang mengairi kawasan yang berbeza: satu kebun sayur, sebuah ladang teh dan satu hutan simpan. Kepelbagaian makroinvertebrata yang tinggi direkod pada kaedah pungutan jaring segi empat dan penyampel Surber di sungai berhutan; sungguh pun begitu kelimpahan spesies yang sangat rendah direkod pada penyampel Surber. RV yang agak besar pada pungutan penyampel Surber (RV 36% dan 28%) diperhatikan masing-masing pada anak sungai di kebun sayur dan di ladang teh. Di antara tiga kaedah penyampelan, jaring segi empat adalah paling cekap, memungut kepelbagaian taksa dan bilangan (kelimpahan) makroinvertebrata yang tinggi secara keseluruhan, terutamanya dari anak sungai di kebun sayur dan di ladang teh (RV<25%). Hanya sedikit tangkapan jaring segi empat (<8 sampel) sudah mencukupi untuk menjalankan penilaian biologi kualiti air, tetapi setiap sampel memerlukan masa memproses yang lebih panjang (±20 min) dibanding dengan alat penyampel yang lain. Sebagai kesimpulan, semua alat penyampel adalah sesuai untuk pungutan makroinvetebrata di anak sungai di Malaysia dan mengumpul himpunan yang menghasilkan keputusan kelas kualiti air biologi Family Biotic Index (FBI) dan Biological Monitoring Working Party (BMWP) yang serupa. Namun di sebalik masa pemprosesan yang lebih panjang, jaring segi empat adalah lebih cekap (RV paling rendah) untuk memungut sampel dan lebih sesuai untuk pungutan makroinvertebrata dari anak sungai yang boleh diharung yang dalam, berarus deras dengan substrata yang kasar.